Microtensile strength of resin cement bond to indirect composite treated by different output powers of Er:YAG laser. Issue 4 (13th February 2016) - Garshasbzadeh, Nazanin Zeinab; Mirzaie, Mansoreh; Yassini, Esmaeil; Shahabi, Sima; Benedicenti, Stefano; Angiero, Francesca; Chiniforush, Nasim
ABSTRACT: The study aimed to evaluate the effect of different output powers of Er:YAG laser on microtensile bonding strength of indirect composite to resin cements.36 indirect composite blocks (GC Gradia DA2, Japan) size 15 × 10 × 10 mm 3 were constructed, and divided into 12 groups, as follows:G1: control group (no treatment); Groups G2 to G6: treated with Er:YAG laser (2, 940 nm) in noncontact mode, frequency 20 Hz, pulse duration 470 µs, with output power ranging from 2W to 6W; Groups G7 sandblasting, Groups 8 to G12: as Groups G2 to G 6 with preparatory sandblasting. One specimen from each group was analyzed by SEM; each specimen was fixed to a specialized metal jig using cyanoacrylate (Mitreapel, Beta Kimya San. Ve TIC, Iran) and debonded under tension with a universal testing machine (Zwick, Germany) at a crosshead speed of 0.5 mm min −1 . Sandblasting and laser can improve bond strength above an energy level of 150 mJ. SEM evaluation of laser‐treated specimens showed irregularities and deep undercuts. T test analysis showed no significant difference between sandblasted and non‐sandblasted group, with laser output power of 0, 100, or 150 mJ ( P = 0.666, P = 0.875, and P = 0.069); in the specimens irradiated with energy output of 200, 250, or 300 mJ, sandblasted specimens showed higher bond strength than non‐sandblasted ones. The results demonstrate that, in composite resin irradiated with laser at energy output of 200–300 mJ, sandblasting might be a suitable procedure to enhance bond strength of resin cement. Microsc. Res. Tech. 79:328–333, 2016 . © 2016 Wiley Periodicals, Inc.